Evaluation of the cost-effectiveness of the treatment of uncomplicated severe acute malnutrition by lady health workers as compared to an outpatient therapeutic feeding programme in Sindh Province, Pakistan - Eleanor Rogers; Saul Guerrero; Deepak Kumar; Sajid Soofi; Shahid Fazal; Karen Martínez; Jose Luis Alvarez Morán; Chloe Puett (BMC, 2019)
Abstract Background Due to the limited evidence of the cost-effectiveness of Community Health Workers (CHW) delivering treatment for severe acute malnutrition (SAM), there is a need to better understand the costs incurred by both implementing institutions and beneficiary households. This study assessed the costs and cost-effectiveness of treatment for cases of SAM without complications delivered by government-employed Lady Health Workers (LHWs) and complemented with non-governmental organisation (NGO) delivered outpatient facility-based care compared with NGO delivered outpatient facility-based care only alongside a two-arm randomised controlled trial conducted in Sindh Province, Pakistan. Methods An activity-based cost model was used, employing a societal perspective to include costs incurred by beneficiaries and the wider community. Costs were estimated through accounting records, interviews and informal group discussions. Cost-effectiveness was assessed for each arm relative to no intervention, and incrementally between the two interventions, providing information on both absolute and relative costs and effects. Results The cost per child recovered in outpatient facility-based care was similar to LHW-delivered care, at 363 USD and 382 USD respectively. An additional 146 USD was spent per additional child recovered by outpatient facilities compared to LHWs. Results of sensitivity analyses indicated considerable uncertainty in which strategy was most cost-effective due to small differences in cost and recovery rates between arms. The cost to the beneficiary household of outpatient facility-based care was double that of LHW-delivered care. Conclusions Outpatient facility-based care was found to be slightly more cost-effective compared to LHW-delivered care, despite the potential for cost-effectiveness of CHWs managing SAM being demonstrated in other settings. The similarity of cost-effectiveness outcomes between the two models resulted in uncertainty as to which strategy was the most cost-effective. Similarity of costs and effectiveness between models suggests that whether it is appropriate to engage LHWs in substituting or complementing outpatient facilities may depend on population needs, including coverage and accessibility of existing services, rather than be purely a consideration of cost. Future research should assess the cost-effectiveness of LHW-delivered care when delivered solely by the government. Trial registration NCT03043352, ClinicalTrials.gov. Retrospectively registered.